1989
DOI: 10.1177/000348948909800511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on Fixation Suppression Ability in Normal Subjects: The Need for Temperature-and Age-Dependent Normal Values

Abstract: The purpose of the present investigation was to determine whether temperature has an effect on the magnitude of fixation suppression (FS) in normal subjects. The subject population consisted of 23 patients ranging in age from 35 to 74 years (mean age of 58.13 years). Each subject received a conventional vestibulometric test battery that included bithermal caloric testing and the FS test. The warm caloric media elicited larger nystagmus slow-phase eye velocities than the cool caloric media. Following warm calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Consequently, the discrepancy between warm and cool irrigations increases with advancing age, which became significant in our three oldest age groups. In parallel with the increasing SCV values, fixation index values increased with age for the warm irrigations, which corresponded with the results of Jacobson and Henry (1989). The poorer fixation abilities in the older subjects could be attributed to age-related deterioration of anatomical structures, such as the cerebellar flocculus, pons, and mesencephalic visual centers, which are responsible for this fixation (Jacobson & Henry 1989).…”
Section: Discussionsupporting
confidence: 75%
“…Consequently, the discrepancy between warm and cool irrigations increases with advancing age, which became significant in our three oldest age groups. In parallel with the increasing SCV values, fixation index values increased with age for the warm irrigations, which corresponded with the results of Jacobson and Henry (1989). The poorer fixation abilities in the older subjects could be attributed to age-related deterioration of anatomical structures, such as the cerebellar flocculus, pons, and mesencephalic visual centers, which are responsible for this fixation (Jacobson & Henry 1989).…”
Section: Discussionsupporting
confidence: 75%
“…25,26 We considered central signs to comprise at least one of the following findings: (1) disorganised pursuit and reduction of pursuit gain; (2) saccades dysmetria with undershoot, overshoot, or asymmetrical latency or velocity; (3) rebound nystagmus; (4) visual fixation suppression of nystagmus of less than 60 per cent; (5) pure vertical or torsional spontaneous or positional nystagmus; or (6) positional nystagmus when bilateral, beating to the uppermost or lowermost ear, showing no latency, low frequency, lack of fatiguability and habituation, without concomitant vertigo. 27,28 The severity of dizziness was measured by the 25-item Dizziness Handicap Inventory scale, which generated a total score (range zero to 100) which indicated the patient's self-perceived level of handicap associated with their dizziness. The results of the Dizziness Handicap Inventory scale are divided into emotional, physical and functional subscales.…”
Section: Methodsmentioning
confidence: 99%
“…However, most authors did find differences between warm and cool temperatures. Higher SCV values for warm compared to cool water irrigations were demonstrated by Mehra (1964), Bruner & Norris (1971), Sills et al (1977), Ford & Stockwell (1978), O'Neill (1978), and Jacobson & Henry (1989), while Greven et al (1979), Press et al (1979, and Karlsen et al (1992) found higher responses for the cool temperature. For air, Munro & Higson (1996) suggested that insufflation temperatures equidistant from body temperature do not result in a symmetrical SCV response.…”
Section: Order Effect and Priming Effectmentioning
confidence: 89%
“…The 95% confidence intervals were calculated on the basis of two standard deviations. Most authors (Mehra, 1964;Capps et al, 1973;Sills et al, 1977;Benitez et al, 1978;Ford & Stockwell, 1978;O'Neill, 1978;Greven et al, 1979;Press et al, 1979;Jacobson & Henry, 1989;Karlsen et al, 1992;Munro & Higson, 1996;Henry, 1999;Van der Stappen et al, 2000) supply for separate warm and cool normative data for the parameters SCV, and frequency. To be able to compare literature data with the present results, the mean, standard deviation and 95% confidence intervals for both temperatures are also depicted in Table 1.…”
Section: Reference Valuesmentioning
confidence: 99%